LIGHTING DESIGN SCHEMES AND COLOURS IN DANCE PERFORMANCES: THE MAGICAL ILLUSION - Basa, Murali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Dance is a creative expression of movements, patterns, and stories they perform. The lighting design contributes to a complete theatrical experience for the audience by highlighting and framing every movement in each dance piece at the right moment. In solos and duets, lighting can emphasize this intimacy by using different spotlights in a particular area and it can make the rest of the stage dark. Different lighting fixtures will help by adding texture to the dance performances. The ambient lighting helps to set the scene, often shadow lighting, and backlighting produces striking images to elevate the body lines and also emphasize the shapes and angles. Few dance groups perform with the integrity of new technologies and Body. This article aims to attempt a definitive and comprehensive illustration of how light design plays an important role in contemporary performances. The lighting design as an art form within the theater is certainly a creative process that illuminates the performer’s body to create a visual bonanza experienced by the spectator. In contemporary dance performances, it became an essential illustrative medium rather than decorative elements like in some traditional dance performances. Lighting design is a scenic art in contemporary dance performances concerned with atmosphere and ’body form’ in relation to the performance space. The lighting design for a performance with a style and colour on a performer’s body creates the magical illusion that is being experienced by the audience. Combinations of lighting design styles and body pigment are crucial and Indian contemporary dance groups adopted such technologies and make some interesting performances. This study analyzes how lighting design influences dance works as a creative approach to performance-making. Blending of costume, makeup, set, interactive media, and lighting design is an added advantage that we can observe in these Indian contemporary Performances. This paper analyzes how lighting design and dance are an integral part of a colorful performance.